Mammalian Ichnopathology: A case study of Holartic Ungulates (Gomphotheriidae, Equidae, Camelidae) of the Late Pleistocene of South America. Ichnotaxomic implications - Oliva, Cristian Marcelo (2018)
The analysis of paleoichnites and trackways corresponding to Holarctic ungulates, from the late Pleistocene (Lujanian Stage/Age) of Pehuen Co and Laguna del Monte tracksites (Buenos Aires Province, Argentina), allows the recognition of several clinical signs (ichnopathologies) that reflect some of the main pedal affections and alterations experienced by living members of the group. Proboscipeda australis (Aramayo and Manera de Bianco, 1987a) presents occasional fissures on its hoofprints, interpreted as fractures on the hornwall (vertical) and cracking of the sole (horizontal). Hippipeda isp. exhibits a series of morphologic anomalies in the digital impression, linked to contracted heel (transversely compressed hoof, narrowing and distal projection of talonar region, with an approximation of both heel-bulb impressions and an enlargement of the spacing between frog baseline and heel buttresses), distorted hoof (asymmetrical sole region and hoof wall, with forwardly projected internal pillar [toe-quarter junction] and anteriorly displaced external heel buttress), turkish-slipper foot (over-elongated hoofprint, showing hyper-lengthening of lateral walls [inner and outer quarters], and hypertrophy of frog and bars). Lamaichnum guanicoe Aramayo and Manera de Bianco, 1987b displays eventual evidence of horny overgrowth: inward/subparallel (loss of bilateral symmetry, medial curving of digits, uneven sizing of toepad prints) and outward/divergent (lateral curving of digits, overexpansion of interclavular gap [with ample separation between both digital ends], enlargement and widening of the tracks, normal acquisition of a secondary heteropody). These intraspecific variations (ichnopathological characters) are often used to segregate a second llamoid ichnospecies: Lamaichnum tulipensis (Aramayo and Manera de Bianco, 1987b), herein proposed as teratologic synonym of Lamaichnum guanicoe.